2011
DOI: 10.1523/jneurosci.6567-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Parietal Interhemispheric Connections in Humans

Abstract: Visuospatial abilities are preferentially mediated by the right hemisphere. Although this asymmetry of function is thought to be due to an unbalanced interaction between cerebral hemispheres, the underlying neurophysiological substrate is still largely unknown. Here, using a method of trifocal transcranial magnetic stimulation, we show that the right, but not left, human posterior parietal cortex exerts a strong inhibitory activity over the contralateral homologous area by a short-latency connection. We also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 55 publications
7
110
0
Order By: Relevance
“…This is also consistent with our finding showing that left-sided extinction errors peaked late around 20-30 min after stimulation. The findings fit with models arguing for mechanisms of interhemispheric competition with a right hemisphere advantage (Hilgetag et al, 2001;Kinsbourne, 1977;Koch et al, 2011), indicating that abnormal interhemispheric interactions likely mediate our observed asymmetry of visuospatial functions (Battelli, Alvarez, Carlson, & Pascual-Leone, 2009;Müri et al, 2002;Plow et al, 2014). An alternative explanation for our results is that right-PPC stimulation induced breakdown of right PPC functions together with a breakdown of left PPC functions, conveyed through callosal inhibition.…”
Section: Discussionsupporting
confidence: 84%
“…This is also consistent with our finding showing that left-sided extinction errors peaked late around 20-30 min after stimulation. The findings fit with models arguing for mechanisms of interhemispheric competition with a right hemisphere advantage (Hilgetag et al, 2001;Kinsbourne, 1977;Koch et al, 2011), indicating that abnormal interhemispheric interactions likely mediate our observed asymmetry of visuospatial functions (Battelli, Alvarez, Carlson, & Pascual-Leone, 2009;Müri et al, 2002;Plow et al, 2014). An alternative explanation for our results is that right-PPC stimulation induced breakdown of right PPC functions together with a breakdown of left PPC functions, conveyed through callosal inhibition.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, interhemispheric somatosensory inhibition in SII peaked later and lasted over a longer range of C-T intervals compared with interhemispheric motor inhibition, regardless of whether the latter is mediated directly via connections between MI (Ferbert et al, 1992) or via connections between homologous PPC (Koch et al, 2011). In contrast to MI, SII serves as a higher-order area, i.e., it integrates information from other somatosensory areas.…”
Section: Temporal Dynamics Of Somatosensory Callosal Connectivitymentioning
confidence: 90%
“…Additionally, clinical studies have indicated that left-hemispheric lesions in the IPL may cause Wernicke's aphasia and primary progressive aphasia, since the language system is mostly left-lateralized (Amici et al, 2006;GornoTempini et al, 2004;Mesulam, 2001;Ojemann, 1979). Recently, asymmetry has also been identified in human parietal interhemispheric anatomical connections (Koch et al, 2011). Given this asymmetry and the fact that Mars et al (2011) found extensive localization within the RIPL, exploring the functional and anatomical subdivisions of the LIPL is necessary.…”
Section: Introductionmentioning
confidence: 99%